2021
DOI: 10.1007/s40670-021-01350-7
|View full text |Cite
|
Sign up to set email alerts
|

Required Longitudinal Service-Learning and Its Effects on Medical Students’ Attitudes Toward the Underserved

Abstract: Although medical students enter medicine with altruistic motives and seek to serve indigent populations, studies show that medical students’ attitudes towards the undeserved tend to worsen significantly as they go through their medical education. This finding emphasizes the need for medical educators to implement activities such as service-learning that may help mitigate this negative trend.All students at the University of Nevada Las Vegas (UNLV) School of Medicine are required to participate in longitudinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Our study results suggest that regardless of the format, it is the tangible interaction of medical students with MUC that has the most meaningful impact on student attitudes, knowledge, and readiness. This is supported by prior studies in which only service learning activities that had direct interaction with underserved communities were successful in sustaining medical student attitudes toward the underserved [ 14 ]. For example, students in our hybrid cohort increasingly rated rurality as a significant factor impacting access to medical care after hearing stories from community members living in food deserts without reliable transportation.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Our study results suggest that regardless of the format, it is the tangible interaction of medical students with MUC that has the most meaningful impact on student attitudes, knowledge, and readiness. This is supported by prior studies in which only service learning activities that had direct interaction with underserved communities were successful in sustaining medical student attitudes toward the underserved [ 14 ]. For example, students in our hybrid cohort increasingly rated rurality as a significant factor impacting access to medical care after hearing stories from community members living in food deserts without reliable transportation.…”
Section: Discussionsupporting
confidence: 60%
“…A recent curricular intervention using required longitudinal service learning at the University of Nevada Las Vegas supports this theory. Students were paired with one of over 50 community service organizations to collaborate on service projects, revealing stable and sustained positive attitudes toward the underserved throughout undergraduate medical education [ 14 ]. At the Dartmouth Geisel School of Medicine, we developed a longitudinal community health elective for first-year medical students that combined classroom didactics with experiential service learning.…”
Section: Introductionmentioning
confidence: 99%
“…Society maintains a critical need for physicians who care for urban underserved patient populations. Prior research has demonstrated that medical students’ attitudes toward underserved populations may decline during medical school 1–3 . These findings create an imperative for medical educators to develop curricular interventions that sustain students’ service orientation and ensure a workforce that meets societal needs.…”
mentioning
confidence: 99%
“…Prior research has demonstrated that medical students' attitudes toward underserved populations may decline during medical school. [1][2][3] These findings create an imperative for medical educators to develop curricular interventions that sustain students' service orientation and ensure a workforce that meets societal needs. Curricular innovations show promise for increasing student engagement with urban underserved populations as manifested by their stated interest in working with these populations in the future.…”
mentioning
confidence: 99%